Identification of a novel X-linked arginine-vasopressin receptor 2 mutation in nephrogenic diabetes insipidus: Case report and pedigree analysis - Peng, Danxia (Medicine (Baltimore), 2019)
INTRODUCTION: The clinical and genetic characteristics of nephrogenic diabetes insipidus (NDI) were described via assessing 2 cases of NDI patients from a Chinese family. PATIENT CONCERNS: Two patients who manifest polyuria and polydipsia were admitted to hospital for definite diagnosis. DIAGNOSIS: Water deprivation-vasopressin tests showed that the patients may possess renal-origin diabetes insipidus. All the levels of thyroid-stimulating hormone, luteinizing hormone, follicle stimulation hormone, adrenocorticotropic hormone, prolactin, and growth hormone in both patients were normal. These results were certified that both patients possess a nephropathy-type diabetes insipidus. B-mode ultrasonography and urinalysis test demonstrated that the patient's diabetes insipidus is unlikely to originate from renal organic disease. Remarkably, by nucleotide sequencing, we found a novel mutation c.414_418del in arginine-vasopressin receptor 2 (AVPR2) was related to the disease of NDI. INTERVENTIONS: Two patients were treated with oral hydrochlorothiazide and indomethacin. In addition, low salt diet and potassium supplementation throughout the patients’ treatment. OUTCOMES: The clinical symptoms of 2 patients were significantly reduced after targeted therapy. CONCLUSION: A mutation in AVPR2 was discovered to be associated with NID. It provides a new target for molecular diagnosis of NDI, enabling families to undergo genetic counseling and obtain prenatal diagnoses.